2018
DOI: 10.3390/su10093091
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Thermal Comfort Potential in Mediterranean Office Buildings: A Case Study of Torre Sevilla

Abstract: The design and construction of buildings is currently subject to a growing set of requirements concerning sustainability and energy efficiency. This paper shows a case study of the Torre Sevilla skyscraper, located in the city of Seville (in the south of Spain), which has high-tech energy-efficient features and which uses air-conditioning systems during most of its operating hours. The analysis carried out starts from a simulation in which occupants’ thermal comfort are obtained, based on the adaptive comfort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…In many previous studies [23,24,[37][38][39], the PMV model and adaptive model as described in CIBSE Guide [40], EN 15251 [41], and ASHRAE Standard55 [31] were compared…”
Section: Thermal Comfort Criteriamentioning
confidence: 99%
“…In many previous studies [23,24,[37][38][39], the PMV model and adaptive model as described in CIBSE Guide [40], EN 15251 [41], and ASHRAE Standard55 [31] were compared…”
Section: Thermal Comfort Criteriamentioning
confidence: 99%
“…Research performed in southern Spain adopted a case-study approach, by concentrating on an energy-efficient, high-tech skyscraper that produced savings in terms of occupation hours, which reduced the use of air-conditioning by 28% and also significantly decreased the overall amount of energy consumed [16]. Research on how the adaptive thermal-comfort module on the amount of energy consumed by buildings was performed on a standard residential structure situated on the University of Newcastle campus, located in Australia, determined that the use of an adaptive strategy could generate considerable savings, related to cooling and heating energy, of up to 70% in temperate climate zones [17][18][19][20][21].…”
Section: Low-energy Buildings Through Passive Designmentioning
confidence: 99%
“…Other researchers [50] confirm that regional adaptive comfort indicators showed more reliable results than the ASHRAE adaptive model for school buildings in the Mediterranean climate. A similar study in the same country [51] applied adaptive thermal comfort in Mediterranean office buildings. They found that natural ventilation through window openings (manual or mechanical) provided up to 30% more occupancy hours that are comfortable based on the EN 15251:2007 standard, and with window-material improvements, that percentage could be raised to more than 50%.…”
Section: Window Design In Relation To Co 2 and Thermal Comfort In Naturally Ventilated Buildingsmentioning
confidence: 99%